2022
DOI: 10.3390/fintech1030017
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Fungible Token (NFT) Market and Its Relationship with Bitcoin and Ethereum

Abstract: Non-fungible tokens (NFTs) are transferrable rights to digital assets, such as art, in-game items, collectables, or music. The phenomenon and its markets have grown significantly since early 2021. We investigate the interrelationships between NFT sales, NFT users (unique active blockchain wallets), and the pricing of Bitcoin (BTC) and Ether (ETH). Using daily data between January 2018 and April 2021, we show that a Bitcoin price shock triggers an increase in NFT sales. Also, Ether price shocks reduce the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(57 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…There is a connection between NFT and cryptocurrency sales, and both markets promise perspectives and risks [32], [33]. A systematic study about the opportunities and challenges of NFTs was given in [34].…”
Section: A the Pyramid Schemementioning
confidence: 99%
“…There is a connection between NFT and cryptocurrency sales, and both markets promise perspectives and risks [32], [33]. A systematic study about the opportunities and challenges of NFTs was given in [34].…”
Section: A the Pyramid Schemementioning
confidence: 99%
“…Although studies [22] and [23] showed that volatility transmission effects between cryptocurrencies and NFTs are limited, Ante [24] revealed that a BTC price shock caused an increase in NFT sales. Furthermore, between BTC and Ethereum (ETH), a bidirectional relationship between returns and long-term spillovers was found.…”
Section: Extended Lppls Modelmentioning
confidence: 99%
“…Some of the well-known ones used are Bitcoin (BTC) and Ethereum (ETH). Thus, transactions related to NFTs of various types do not use the real currency that we know today, instead, they use the cryptocurrencies (Ante, 2022).…”
Section: Tradabilitymentioning
confidence: 99%